Kingdee - Zhao, Ziqian; McFarlan, F. Warren (Franklin Warren); Zhang, Jin ([London] : SAGE, 2016)
On June 8th, 2007, afternoon, in Kingdee's Shenzhen headquarter (see Appendix I), everyone was enjoying beer and wine. Almost everything in both personal life and career was being discussed. This was the Kingdee's weekly signature event 'beer bust,' a regular 'big event' in these people's schedules. This was where Kingdee's 'people culture'" was first brought into public attention.
Originally Published in: Zhao, Z., McFarlan, F. W., & Zhang, J. (2011). Kingdee. 6-311-351. Beijing: Tsinghua SEM China Business Case Center.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; Kingdee (Firm); Corporate culture -- Case studies; Competition -- Case studies; Consolidation and merger of corporations -- Case studies